Mengatasi pengangguran di Indonesia: Peran industri perhutani, kewirausahaan muda, dan kepemimpinan sebagai landasan pembangunan ekonomi berkelanjutan - rahmadhina, ade ayu (Maliki Interdisciplinary Journal, 2026)
Unemployment remains a structural issue that disrupts Indonesia’s economic progress and social stability, with the national unemployment rate recorded at 5.86% in the second quarter of 2024. This article explores a set of integrated strategies aimed at lowering unemployment by examining the contribution of the forestry sector as a provider of labor opportunities, the role of young entrepreneurs in generating new jobs, and the importance of crisis leadership in ensuring the success of policy implementation. The study adopts a qualitative analytical approach using secondary data sourced from the Central Bureau of Statistics (BPS), Perhutani’s reports, and relevant empirical literature. The findings reveal that the forestry industry in Kediri employs approximately 12,500 local workers, young entrepreneurs contribute to 35% of newly created jobs in the MSME sector, and adaptive leadership can enhance the effectiveness of government programs by up to 40%. Based on these results, the article presents sustainable and integrated policy recommendations aimed at addressing unemployment challenges in Indonesia.